2022
DOI: 10.1155/2022/9646846
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Model of Residual Neural Network for Pathological Confirmed Lymph Node Metastasis of Ovarian Cancer

Abstract: Purpose. We want to develop a model for predicting lymph node status based on positron emission computed tomography (PET) images of untreated ovarian cancer patients. We use the feature map formed by wavelet transform and the parameters obtained by image segmentation to build the model. The model is expected to help clinicians and provide additional information about what to do with first-visit patients. Materials and Methods. Our study included 224 patients with ovarian cancer. We have chosen two main methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Results showed that the model achieved high accuracy, AUC, sensitivity, and specificity on the training set (accuracy: 88.54%, AUC: 0.94, sensitivity: 98.65%, specificity: 79.52%) and the test set (accuracy: 91.04%, AUC: 0.92, sensitivity: 81.25%, specificity: 100%). In conclusion, the study displays the effectiveness of wavelet transform and the residual neural network in predicting lymph node metastasis in ovarian cancer patients, providing valuable insights for patient staging and treatment decisions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results showed that the model achieved high accuracy, AUC, sensitivity, and specificity on the training set (accuracy: 88.54%, AUC: 0.94, sensitivity: 98.65%, specificity: 79.52%) and the test set (accuracy: 91.04%, AUC: 0.92, sensitivity: 81.25%, specificity: 100%). In conclusion, the study displays the effectiveness of wavelet transform and the residual neural network in predicting lymph node metastasis in ovarian cancer patients, providing valuable insights for patient staging and treatment decisions [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the sample size of this study was small and the credibility of the conclusions is speculative. Yao et al [ 28 ] developed a model for predicting the lymph node status based on PET images of patients with ovarian cancer using residual neural networks and SVM for modeling. Their model had an AUC of 0.92 in the test cohort, but the model only included patients with early-stage ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hypermetabolic LN on PET/CT, initial CA125 ≥ 500, and initial peritoneal cancer index ≥ 10 were independently and signi cantly associated with pelvic and/or para-aortic LNM 26,27 . Recently, many researchers have focused on radiomics features of PET/CT or contrast-enhanced CT in predicting LNM in AEOC, among which LNM assessment has been proven to have a certain signi cant improvement 28,29 . However, the manually timeconsuming delineation of ROI and complex models limit its clinical application.…”
Section: Introductionmentioning
confidence: 99%